TBHP-promoted direct oxidation reaction of benzylic Csp3–H bonds to ketones. Issue 25 (7th March 2017) - Tan, Jiajing; Zheng, Tianyu; Yu, Yuqi; Xu, Kun
Abstract : A metal-free oxidation system employing tert -butyl hydroperoxide (TBHP) has been developed for selective oxidation of structurally diverse benzylic sp 3 C–H bonds. Abstract : A metal-free oxidation system employing tert -butyl hydroperoxide (TBHP) has been developed for selective oxidation of structurally diverse benzylic sp 3 C–H bonds. This low-cost methodology allows for rapid generation of synthetically and biologically valued arylketones in good to excellent yields from readily available alkylarenes and diarylmethanes.